1978
DOI: 10.1073/pnas.75.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Affinity purification of cardiac adenylate cyclase: dependence on prior hydrophobic resolution.

Abstract: The interaction of cardiac adenylate cyclase [ATP pyrophosphate-lyase (cyclizing); EC 4.6.1.11 with a variety of nucleotide affinity resins was systematically investigated. None of these resins effectively bound the native, detergentsolubilized enzyme. However, after hydrophobic resolution on an uncharged resin consisting of long-chain alkyl groups linked to agarose via ether bonds, 40% of the adenylate cyclase activity biospecifically adsorbed to an ATP affinity resin. Gel filtration without detergent after h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…This may in part be explained by its extreme instability and by the lack of suitable ligands for construction of affinity supports which otherwise proved to be extremely useful for isolation of minute quantities of total cellular protein [9,10]. The most notable success in purification of adenylate cyclase has been achieved with the canine myocardial enzyme by successive hydrophobic and affinity chromatography on ATP-agarose [11]. However, the procedure in [11] failed to resolve C and G since the purified material was still activated by Gpp(NH)p. The first successful separation of the catalyst and the regulatory G-protein has been achieved by *To whom correspondence should be addressed affinity chromatography of solubilized pigeonerythrocyte membrane adenylate cyclase on GTPSepharose: While the G-protein was selectively retained by the resin, the catalytic part was exclusively found in the column pass-through [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may in part be explained by its extreme instability and by the lack of suitable ligands for construction of affinity supports which otherwise proved to be extremely useful for isolation of minute quantities of total cellular protein [9,10]. The most notable success in purification of adenylate cyclase has been achieved with the canine myocardial enzyme by successive hydrophobic and affinity chromatography on ATP-agarose [11]. However, the procedure in [11] failed to resolve C and G since the purified material was still activated by Gpp(NH)p. The first successful separation of the catalyst and the regulatory G-protein has been achieved by *To whom correspondence should be addressed affinity chromatography of solubilized pigeonerythrocyte membrane adenylate cyclase on GTPSepharose: While the G-protein was selectively retained by the resin, the catalytic part was exclusively found in the column pass-through [2].…”
Section: Introductionmentioning
confidence: 99%
“…The most notable success in purification of adenylate cyclase has been achieved with the canine myocardial enzyme by successive hydrophobic and affinity chromatography on ATP-agarose [11]. However, the procedure in [11] failed to resolve C and G since the purified material was still activated by Gpp(NH)p. The first successful separation of the catalyst and the regulatory G-protein has been achieved by *To whom correspondence should be addressed affinity chromatography of solubilized pigeonerythrocyte membrane adenylate cyclase on GTPSepharose: While the G-protein was selectively retained by the resin, the catalytic part was exclusively found in the column pass-through [2]. Resolution of G and C by means of gel-filtration in the presence of cholate and high concentrations of ammonium sulfate has been reported independently by two groups [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[53] for 5'-nucleotidase ( M , 140000-150000); [51] for leucine aminopeptidase ( M , 320000) and [55] for y-glutamyltransferase ( M , It has been stressed [28] recently that hydrophobic membrane proteins such as adenylate cyclase are capable of interacting strongly with other membrane proteins thus leading to an apparent increase in their molecular weight. Hydrophobic chromatography has been proposed to promote separation of adenylate cyclase from other proteins of varying hydrophobicity [28].…”
Section: Smentioning
confidence: 99%
“…The non-ionic detergents (Triton X-100 or Lubrol PX) which have been used have a very similar Hydrophilic Lipophilic Balance number (13.5 and 13.8). In a few cases, it has been established that cyclase activity was preserved in the absence of detergent [3, 27,28], but at the expense of an aggregation of the enzyme molecule, incompatible with further biophysical studies. Even when the solubilization process was performed under optimal conditions, all the cyclase systems studies have been shown to differ markedly with respect to their yield of solubilization and specific activity, stability, sensitivity to hormonal and nonhormonal effectors, and size.…”
mentioning
confidence: 99%
“…1]-has been only partially purified from mammalian tissues (15,16) or E. coli (17,18). The instability of the enzyme activity and the low abundance of the protein have accounted for the difficulty in its purification.…”
mentioning
confidence: 99%